Access to 3D Alicyclic Amine-Containing Fragments through Transannular C–H Arylation - Lee, Melissa; Adams, Ashley; Cox, Philip B.; Sanford, Melanie S. (Synlett, 2019)
In this Letter, we adapt a recently reported Pd-catalyzed transannular C(sp3)–H arylation of alicyclic amines for applications in fragment-based drug discovery (FBDD). We apply this method to the synthesis of a series of 6-arylated 3-azabicyclo[3.1.0]hexanes that are rule-of-three compliant fragments. Several modifications were made to the Pd-catalyzed C–H arylation method to enhance its utility in fragment synthesis. These include the use of microwave heating to shorten reaction times to under 1 h and the development of new approaches for directing group cleavage. Finally, we demonstrate that this fragment library falls within desirable physicochemical space for FBDD applications.
Keywords: directed C–H functionalization; fragment based drug discovery; amines; palladium; arylation; microwave; directing group